Future land use maps for the Netherlands based on the Dutch One Health Shared Socio-economic Pathways - Martha Dellar; Gertjan Geerling; Kasper Kok; Peter M. van Bodegom; Gerard van der Schrier; Maarten Schrama; Eline Boelee (Scientific Data, 2024)
Abstract To enable detailed study of a wide variety of future health challenges, we have created future land use maps for the Netherlands for 2050, based on the Dutch One Health Shared Socio-economic Pathways (SSPs). This was done using the DynaCLUE modelling framework. Future land use is based on altitude, soil properties, groundwater, salinity, flood risk, agricultural land price, distance to transport hubs and climate. We also account for anticipated demand for different land use types, historic land use changes and potential spatial restrictions. These land use maps can be used to model many different health risks to people, animals and the environment, such as disease, water quality and pollution. In addition, the Netherlands can serve as an example for other rapidly urbanising deltas where many of the health risks will be similar.